P125 Heroin Smoking is Associated with Early Onset COPD with Predominant Emphysema. (14th November 2013) - Walker, PP; Thwaite, E; Amin, S; Curtis, J; Calverley, PM
Abstract : An association between opiate smoking and acute severe asthma is recognised but a relationship with COPD is not clearly established and limited to case reports. Anecdotally there is limited knowledge about the pulmonary effects of heroin smoking amongst drug users, drug service workers and healthcare professionals. To examine this relationship we studied a convenience sample of 41 heroin smokers who presented to our service with respiratory symptoms and were diagnosed with COPD. All completed spirometry and underwent a CT scan while 20 had alpha-1-antitrypsin level measured and 9 had DLco measured. Visual emphysema extent was recorded by two thoracic radiologists with a third adjudicating where there was a more than 1 point difference in grading. Emphysema was assessed in both lungs at 3 levels (cranial, middle and caudal) with grade 1 representing 1–5% emphysema, 2 = 6–25% emphysema, 3 = 26–50%, 4 = 51–75% and 5 >75% emphysema. Mean age at presentation was 40.7 (SD 5.4) years with all subjects aged 50 years or younger and 18/41 (44%) were younger than 40 years. Mean pack years cigarette smoking was 27 (19) and subjects had smoked heroin for 14.8 (6.6) years. Mean pre-bronchodilator FEV1 was 0.99 (0.52) L; 29.9 (17.6)%predicted and FEV1/FVC was 0.36 (0.13). Nine subjects had moderate (GOLD stage II), 7 severe (GOLD stage III) and 25 had very severe (GOLD stage IV) COPD. DLco was 41 (23)%predicted in the 9 subjects and alpha-1-antitrypsin level was normal in the 20 subjects who had it measured. Twenty nine CT scans were high resolution and suitable for detailed analysis. 28/29 (97%) subjects had at least grade 1 upper lobe emphysema and mean upper lobe emphysema extent (average of the 2 upper lobe scores) was 3.0 (1.4) with 15/29 (52%) subjects having grade 3 emphysema or worse. Overall emphysema extent (average of all 6 scores) was 2.5 (1.1). Moderate bronchiectasis was seen on only 3 scans and no subject had severe bronchiectasis. The other 12 CT scans could not be precisely graded but all had been reported as showing emphysema (2 mild, 2 moderate, 1 moderate to severe and 7 severe). Heroin smoking is associated with very early onset severe COPD with predominant emphysema. This is an important public health message needing dissemination to heroin smokers, drug service workers and healthcare professionals.